Embedded systems architecture : discover software programming on embedded devices to build safe and secure connected systems - Lacamera, Daniele (PACKT Publishing Limited, 2023)
Design safe and reliable software for embedded systems and explore the internals of device drivers, RTOS, and TEE Key Features Identify and overcome challenges in embedded environments Understand and implement the steps required to increase the security of IoT solutions Build safety-critical and memory-safe parallel and distributed embedded systems Book DescriptionEmbedded Systems Architecture begins with a bird's-eye view of embedded development and how it differs from the other systems that you may be familiar with. This book will help you get the hang of the internal working of various components in real-world systems. You'll start by setting up a development environment and then move on to the core system architectural concepts, exploring system designs, boot-up mechanisms, and memory management. As you progress through the topics, you'll explore the programming interface and device drivers to establish communication via TCP/IP and take measures to increase the security of IoT solutions. Finally, you'll be introduced to multithreaded operating systems through the development of a scheduler and the use of hardware-assisted trusted execution mechanisms. With the help of this book, you will gain the confidence to work with embedded systems at an architectural level and become familiar with various aspects of embedded software development on microcontrollers-such as memory management, multithreading, and RTOS-an approach oriented to memory isolation. What you will learn Participate in the design and definition phase of an embedded product Get to grips with writing code for ARM Cortex-M microcontrollers Build an embedded development lab and optimize the workflow Secure embedded systems with TLS Demystify the architecture behind the communication interfaces Understand the design and development patterns for connected and distributed devices in the IoT Master multitasking parallel execution patterns and real-time operating systems Become familiar with Trusted Execution Environment (TEE) Who this book is for If you're a software developer or designer looking to learn about embedded programming, this is the book for you. You'll also find this book useful if you're a beginner or a less experienced embedded programmer on a quest to expand your knowledge on embedded systems.